Simulating Potential Associated Socio-Economic Determinants With Sustainable Food Security (A Macro-Micro Spatial Quantitative Model) - Pakravan-Charvadeh, Mohammad Reza; Flora, Cornelia; Khan, Haider A. (Frontiers in Public Health, 2022)
Improving sustainable food security status, nowadays, is an important challenge globally, ‎especially in developing countries. The policy goal should be equity – everyone has the same ‎opportunity to be food secure – rather than equality – everyone gets the same subsidy. Since ‎the culture and socioeconomic status within a country vary from region to region, collapsing ‎all areas into a unique region may introduce error and inaccurate results, as most studies ‎carried out. This study assesses the geographical pattern of association between food security ‎and socioeconomic factors in urban areas in Iran using a nationally and regionally representative ‎household consumption-expenditure survey during 2010-2018. The logistic regression model and ‎big data are used to achieve the goal. The results show that a substantial number of ‎households face food insecurity in urban areas in Iran. Also, different geographic regions ‎have various salient factors that affect food insecurity. Aggregation tests confirmed that ‎researchers should estimate separate models for different provinces, states, and districts to ‎assess and monitor the food security status of a country instead of the estimation of a unique ‎model for the whole of the country. Geographical disparities should be considered as an ‎important issue before suggesting any catch-all policies for a country. The geo-locational ‎factor of households is a key determinant of the association between socioeconomic factors ‎and food security in urban areas in Iran. In sum, the practical suggestions for improving ‎Iranian households' food security in urban areas are as follows: 1- Developing job ‎opportunities for the head of household; 2- Enhancing the potential for self-employment; 3- ‎Facilitating the study of children within households including providing inexpensive ‎uniforms, books and materials especially for poor households; 4- Supporting young couples in ‎terms of accessing to financial resources and providing inexpensive essential equipment of ‎home for them; and 5- Introduction of the importance of dietary diversity and different foods ‎which can be cooked by using these food ingredients within a household. Comparative case ‎studies using similar methodologies can test if our results are generalizable.